+0

# can anyone help me please with this?

0
339
3
+262

sabi92  Jun 4, 2015

#3
+81029
+13

Here's the algebraic solution without using polar coordinates.....

( x + 6)^2 + ( y - 9)^2 = 52

x^2 + y^2  = 13   →  y^2  = 13 - x^2  →  y = ± √(13 - x^2)

Let us first guess that y = the positive root of √(13 - x^2)

Substitute this into the first equation.........

(x + 6)^2 + ( √(13 - x^2) - 9)^2 = 52       expand

x^2 + 12x  + 36 + 13 - x^2 - 18 √(13 - x^2) + 81 = 52     simplify

12x - 18 √(13 - x^2) = -78   divide through by 6

2x - 3 √(13 - x^2) = -13   rearrange

2x + 13  = 3√(13 - x^2)    square both sides

4x^2 + 52x + 169  = 9(13 - x^2)    simplify

4x^2 + 52x +169 = 117 - 9x^2     rearrange

13x^2 + 52x + 52  = 0       divide through by 13

x^2 + 4x + 4 = 0   factor

(x + 2)^2 = 0   take the square root of both sides

x + 2 = 0     so  x =  -2   and  y = √(13 - x^2)  = √(13 - (-2)^2) = √(13 - 4) = √9 = 3

And we have seen above that (-2, 3) is a solution

----------------------------------------------------------------------------------------------------

Now...let us assume that the negative root of  √(13 - x^2)   also might work for y

The algebra looks eerily similar to what we did before...........

(x + 6)^2 + ( -√(13 - x^2) - 9)^2 = 52

x ^2 + 12x + 36  + 13 - x^2 + 18√(13 - x^2) + 81  = 52

12x + 18√(13 - x^2) = -78

2x + 3√(13 - x^2) = -13

2x + 13  = -3√(13 - x^2)

4x^2 + 52x + 169  = 9(13 - x^2)

4x^2 + 52x + 169 = 117 - 9x^2

13x^2 + 52x + 52 = 0

x^2 + 4x + 4 = 0

(x + 2)^2  = 0

x + 2  = 0   ...  so....    x = -2   and y = -√(13 - x^2)  =- √(13 - (-2)^2) =- √(13 - 4) = -√9 = -3

However...notice the problem in the first equation if y = -3

(-2 + 6)^2 + (-3 - 9)^2  =  4^2 + (-12)^2  =  16 + 144 =  160  and this does not equal 52  !!!

So....we only have one solution.....

--------------------------------------------------------------------------------------------------

See???......I told you it was messy  !!!

Let us offer up our many sacrifices to the Altar of Desmos, The Spirit of the Graphing Calculator

CPhill  Jun 4, 2015
Sort:

#1
+81029
+10

( x + 6)^2 + ( y - 9)^2 = 52

x^2 + y^2  = 13

The Algebra for this one could get a little messy......I might use a graphical approach....

https://www.desmos.com/calculator/cnkpzxaqrm

These are two circles that are tangent to each other....

The only "solution" point occurs at (-2, 3)....... And this is the point of tangency.......

CPhill  Jun 4, 2015
#2
+26403
+10

Here's an algebraic approach (Chris is right - it's a little messy!):

.

Alan  Jun 4, 2015
#3
+81029
+13

Here's the algebraic solution without using polar coordinates.....

( x + 6)^2 + ( y - 9)^2 = 52

x^2 + y^2  = 13   →  y^2  = 13 - x^2  →  y = ± √(13 - x^2)

Let us first guess that y = the positive root of √(13 - x^2)

Substitute this into the first equation.........

(x + 6)^2 + ( √(13 - x^2) - 9)^2 = 52       expand

x^2 + 12x  + 36 + 13 - x^2 - 18 √(13 - x^2) + 81 = 52     simplify

12x - 18 √(13 - x^2) = -78   divide through by 6

2x - 3 √(13 - x^2) = -13   rearrange

2x + 13  = 3√(13 - x^2)    square both sides

4x^2 + 52x + 169  = 9(13 - x^2)    simplify

4x^2 + 52x +169 = 117 - 9x^2     rearrange

13x^2 + 52x + 52  = 0       divide through by 13

x^2 + 4x + 4 = 0   factor

(x + 2)^2 = 0   take the square root of both sides

x + 2 = 0     so  x =  -2   and  y = √(13 - x^2)  = √(13 - (-2)^2) = √(13 - 4) = √9 = 3

And we have seen above that (-2, 3) is a solution

----------------------------------------------------------------------------------------------------

Now...let us assume that the negative root of  √(13 - x^2)   also might work for y

The algebra looks eerily similar to what we did before...........

(x + 6)^2 + ( -√(13 - x^2) - 9)^2 = 52

x ^2 + 12x + 36  + 13 - x^2 + 18√(13 - x^2) + 81  = 52

12x + 18√(13 - x^2) = -78

2x + 3√(13 - x^2) = -13

2x + 13  = -3√(13 - x^2)

4x^2 + 52x + 169  = 9(13 - x^2)

4x^2 + 52x + 169 = 117 - 9x^2

13x^2 + 52x + 52 = 0

x^2 + 4x + 4 = 0

(x + 2)^2  = 0

x + 2  = 0   ...  so....    x = -2   and y = -√(13 - x^2)  =- √(13 - (-2)^2) =- √(13 - 4) = -√9 = -3

However...notice the problem in the first equation if y = -3

(-2 + 6)^2 + (-3 - 9)^2  =  4^2 + (-12)^2  =  16 + 144 =  160  and this does not equal 52  !!!

So....we only have one solution.....

--------------------------------------------------------------------------------------------------

See???......I told you it was messy  !!!

Let us offer up our many sacrifices to the Altar of Desmos, The Spirit of the Graphing Calculator

CPhill  Jun 4, 2015

### 9 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details